PENDAMPINGAN PENYUSUNAN BAHAN AJAR DORATOON DALAM RANGKA MENINGKATKAN PROFESIONALISME GURU DI ERA PEMBELAJARAN DIGITAL - Sundari, Fitri Siti (Universitas Tidar, 2024)
The purpose of this service is to provide understanding to teachers of the importance of compiling interesting teaching materials so that students are more motivated to learn. In addition, after teachers understand the importance of preparing teaching materials, in this PKM activity the teachers are given training in compiling doratoon-based teaching materials, which is one application that combines images and videos. The target of this PkM activity is the teachers of SDN Ciomas 06 which is located at Jl. Kreteg Kaler No.56, Padasuka, Ciomas District, Bogor Regency, West Java 16610. This method of carrying out service is carried out descriptively. Field surveys were conducted to explore the problems faced by partners through observation techniques and interviews with school principals and several teachers. The problem faced by partners is that learning activities are still teacher-centered, thus making students less actively involved in the learning process. Most teachers are still minimal in creating interesting, interactive, and effective learning. This can cause students to lose interest and be less optimal in understanding the material presented. Although learning technology has advanced, most teachers are still not used to making digital teaching materials, making it difficult to develop technology-based learning. The results of the participant survey from this service activity showed that the material provided was easy to understand, the material was very relevant and was in accordance with the needs of participants, the material was enough to equip participants to make Doratoon-based teaching materials, this mentoring material made it easier for participants to make teaching materials. For the delivery of material also get good results, namely the speaker presents the content of the material well, the speaker really understands the material presented, the allocation of time for delivering material and assistance is quite free. For the results of the implementation of service activities, good results were obtained, namely the speaker provided answers to participants' questions clearly, overall the discussion/question and answer has greatly helped increase participants' understanding. For participant satisfaction, all participants are satisfied with the material provided by the speaker, all participants understand the material presented, all participants can make products as a result of mentoring.